Combined Immunodeficiency With Inflammatory Bowel Disease in a Patient With TTC7A Deficiency. Issue 5 (May 2019) - Broome, David T.; Young, Andrew; Torbic, Heather; Krishnan, Sudhir; Gordon, Ilyssa; Lai, Keith; Rizk, Maged; Rieder, Florian
Abstract : ABSTRACT: Tetratricopeptide repeat domain-7A (TTC7A) deficiency causing combined immunodeficiency with inflammatory bowel disease (IBD) is rare. This case report alerts physicians to the possibility of TTC7A deficiency causing combined immunodeficiency with IBD and also highlights some of the current treatment options. We describe a 19-year-old patient with a compound heterozygote TTC7A mutation causing combined immunodeficiency, IBD, and multiple intestinal atresia. Compound heterozygote TTC7A mutations are known to cause combined immunodeficiency and IBD. Although rare, clinicians should be alerted to this variant and should understand the general approach to treatment.